(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In recent years, women's empowerment in India has been a widely discussed field. For empowering women, education is the most important prerequisite. The Beti Bachao Beti Padhao campaign of the present Government is an initiative to create awareness among the Indian populace against gender-based discrimination. Under this scheme, the Government intends to empower the female through education. This awareness about gender equity was very much an essential component of our ancient Indian civilisation, whose progress could be judged from the fact that our education system was non-discriminatory concerning both sexes. Women also had equal rights for their upliftment. They have always been accorded an honourable position in the Indian social system.